Indonesia's Small Entrepreneurs : Trading on the Margins. - Turner, Sarah (Taylor and Francis, 2013)
In the context of Makassar, on the eastern Indonesian island of Sulawesi, the book explores the socioeconomic and cultural relationships that make life for small entrepreneurs in Makassar so distinctive. Using a new framework for the study of small enterprises - the 'small enterprise integrative framework' - this book gives us a greater understanding of the organization and operations of small enterprises in developing countries, at both the micro and macro levels. The application of this new framework for research reveals the diversity of labour flexibility, networking and cluster styles amon.